Exploring the influence of milling time on the structural, elastic, dielectric, morphological, and optical properties of CuSe nanoparticles produced by mechanical alloying - Katibi, Kamil Kayode; Shitu, Ibrahim Garba; Shukla, Arun Kumar; Alotaibi, Khalid M.; Oladipupo, Rukayat Afolake; Muhammad, Haruna (John Wiley and Sons, 2026)
In this study, copper selenide (CuSe) nanoparticles were synthesized using high-energy ball milling with systematically varied milling times to explore their effect on the structural, dielectric, magnetic, and optical properties of the material. X-ray diffraction confirmed single-phase hexagonal CuSe with decreasing crystallite size and increasing microstrain as milling progressed. Raman and electron spin resonance analyses show phonon confinement and defect-induced magnetic suppression. Field emission scanning electron microscopy and transmission electron microscope revealed nanoscale agglomerates, while dielectric studies demonstrated size-dependent permittivity and loss characteristics consistent with Maxwell–Wagner polarization. Optical analysis revealed a bandgap widening from 1.66 to 1.86 eV and a PL peak at 710 nm, confirming quantum confinement effects. Energy-dispersive X-ray spectroscopy (EDS) confirmed the purity and stoichiometry of the samples. Findings of the study establish clear structure–property relationships driven by milling-induced microstructural evolution, demonstrating the tunability of CuSe nanoparticles for dielectric and optoelectronic applications.